2011
DOI: 10.1016/j.eurpsy.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Change in psychiatrists’ attitudes towards the physical health care of patients with schizophrenia coinciding with the dissemination of the consensus on physical health in patients with schizophrenia

Abstract: These results imply that the dissemination of the "Consensus on Physical Health in Schizophrenia Patients", and possibly other actions, has made psychiatrists more aware of an integral approach to patients with schizophrenia, promoting increased monitoring of the physical health of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Two consensus conferences have called on mental health care providers to take responsibility for the physical health of their patients 7,8. However, despite data suggesting that the sensitization of psychiatrists to expand their tasks to include assessments of both mental and physical health in SMI patients can be improved by consensus guidelines 9, many psychiatrists still consider their primary or, even, sole function to provide clinical care in terms of psychiatric symptom control and are reluctant to monitor physical health 6.…”
Section: Barriers To the Recognition And Management Of Physical Diseamentioning
confidence: 99%
“…Two consensus conferences have called on mental health care providers to take responsibility for the physical health of their patients 7,8. However, despite data suggesting that the sensitization of psychiatrists to expand their tasks to include assessments of both mental and physical health in SMI patients can be improved by consensus guidelines 9, many psychiatrists still consider their primary or, even, sole function to provide clinical care in terms of psychiatric symptom control and are reluctant to monitor physical health 6.…”
Section: Barriers To the Recognition And Management Of Physical Diseamentioning
confidence: 99%
“…19 studies utilised SRQs Archie et al, 2007Arbour, Faulkner, & Cohn, 2010;Brown, Birtwistle, Roe, & Thompson, 1999, Brown, Goetz, Van Sciver, Sullivan, & Hamera, 2006Dubbert et al, 2006;Ellingrod et al, 2011;Elmslie, Mann, Silverstone, Williams, & Romans, 2001;Faulkner et al, 2006;Lassenigus, kerlind, Wiklund-Gustin, Arman, & Söderlund, 2013;Lindamer et al, 2008;McLeod, Jaques, & Deane, 2009;Osborn, Nazareth, & King, 2007;Ratliff et al, 2012;Ussher, 2003;Ussher, Doshi, Sampuran, & West, 2011;Van Citters et al, 2010;Vancampfort, Probst, Knapen, Carraro, & De Hert, 2012. Excluded studies (with reason) 55 did not use an outcome measure that provided an assessment of the three fundamental domains of physical activity Acil, Dogan, & Dogan, 2008;Adams, 1995;Aquila, 2000;Archie, Wilson, Osborne, Hobbs, & McNiven, 2003;Ball, Coons, & Buchanan, 2001;Barton, Griffin, & Pretty, 2012;Beebe et al, 2005;Bobes et al, 2010a,b, Bobes, Arango, Garcia-Garcia, & Rejas, 2010bBrill et al, 2007;Brunero & Lamont, 2010;Buhagiar, Parsonage, & Osborn, 2011;Centorrino et al, 2006;Charmove, 1986;Chuang, Mansell, & Pattern, 2008;Crone et al, 2004;Daumit et al, 2005;Davidson et al, 1999Davidson et al, , 2001…”
Section: The Identification Of the Different Outcome Measures Usedmentioning
confidence: 99%
“…Previous studies show that the comorbidity for physical diseases is higher among people with schizophrenia [1][2][3][4][5][6][7][8][9][10]. Buhagiar et al [33] report that people with severe mental illness are not entirely aware of the risks of developing physical diseases.…”
Section: Discussionmentioning
confidence: 97%
“…People with schizophrenia have a high comorbidity for these diseases [1][2][3][4][5][6][7][8][9][10] as well as a higher prevalence of smoking compared with the general population [1][2][3][4][5][6][7][8]11,12] -between 54 and 70% [2,5,6,8,10,13], compared to 14% in the Swedish population [14]. Roick et al [15] showed that people with schizophrenia have a less healthy lifestyle when it comes to diet, exercise and smoking than the general population.…”
Section: Introductionmentioning
confidence: 97%